Implementation of the self-organized learning environments learning model to enhace learning outcomes and student independence - Kusmiyati Kusmiyati (Jurnal Pijar Mipa, 2023)
This study aims to describe student learning outcomes and independence through SOLE (Self Organized Learning Environments) learning. The subjects of this study were 21 Biology Education students who took the Introductory Education course. Data on learning outcomes were collected using tests, while independence using a non-test with a Likert scale. The collected data were analyzed qualitatively into five categories. Cognitive learning outcomes in the good category were 11 (52%), and very good was 10 (48%) students. The results of the analysis of independence with categories fairly good, good, and very good were 2(10%), 8(32%), and 11(52%) students, respectively. The achievement of student independence on the indicators of not depending on others, self-confidence, discipline, responsibility, and self-control varies from fairly good to very good. In contrast, the self-initiative indicators vary in the good and very good categories. The analysis of the relationship between independence and learning outcomes shows that in all categories, independence shows learning outcomes in very good and good categories. Conclusion: (a) Student cognitive learning outcomes in completing lectures vary in very good and good categories. (b) Students' independence in completing lectures varies from fairly good to very good categories but is dominated by very good categories. (c) student independence in each indicator varies from fairly good to very good, except for the initiative indicator, which is in the good and good categories. (d) the level of student independence determines learning outcomes that vary in very good and good categories.